1997
DOI: 10.1073/pnas.94.8.3795
|View full text |Cite
|
Sign up to set email alerts
|

Glucose transporter GLUT3: Ontogeny, targeting, and role in the mouse blastocyst

Abstract: The first differentiative event in mammalian development is segregation of the inner cell mass and trophectoderm (TE) lineages. The epithelial TE cells pump f luid into the spherical blastocyst to form the blastocyst cavity. This activity is fuelled by glucose supplied through facilitative glucose transporters. However, the reported kinetic characteristics of blastocyst glucose transport are inconsistent with those of the previously identified transporters and suggested the presence of a high-affinity glucose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
146
3
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(157 citation statements)
references
References 36 publications
7
146
3
1
Order By: Relevance
“…In that report, GLUT1 was purported to be the main glucose transporter, responsible for uptake of maternal glucose. Pantaleon et al (99) noted, however, that this would be unlikely given that the K m of glucose transport was much lower than that of GLUT1. Gardner and Kaye (43) had demonstrated that the mouse blastocyst had a K m of 6.3 Ϯ 0.5 mM for 3-O-methylglucose (3-OMG) whereas GLUT1's K m for 3-OMG is 20.1 Ϯ 2.9 mM.…”
Section: Glut3 In the Embryomentioning
confidence: 97%
See 1 more Smart Citation
“…In that report, GLUT1 was purported to be the main glucose transporter, responsible for uptake of maternal glucose. Pantaleon et al (99) noted, however, that this would be unlikely given that the K m of glucose transport was much lower than that of GLUT1. Gardner and Kaye (43) had demonstrated that the mouse blastocyst had a K m of 6.3 Ϯ 0.5 mM for 3-O-methylglucose (3-OMG) whereas GLUT1's K m for 3-OMG is 20.1 Ϯ 2.9 mM.…”
Section: Glut3 In the Embryomentioning
confidence: 97%
“…Pantaleon et al (99) first described the expression of this transporter in murine embryos in 1997. GLUT1 and GLUT2 had been identified six years earlier in the murine preimplantation embryo (1, 51).…”
Section: Glut3 In the Embryomentioning
confidence: 99%
“…The different members of the SLC2 family differ in substrate specificity, affinity for cytochalasin B, inhibition by phloretin or phlorizin, and regulation by insulin [11]. Of the 14 SLC2 gene family members, expression of Glut1, Glut2, Glut3, Glut8 and Glut12 (also known as Slc2a1, Slc2a2, Slc2a3, Slc2a8 and Slc2a12) is detected in preimplantation mouse embryos [13][14][15][16][17][18]. GLUT12 protein is not detected in early postimplantation embryos, but it is detected later, during fetal development [17,19].…”
Section: Introductionmentioning
confidence: 99%
“…High levels of GLUT1 and GLUT3 are present in a wide range of fetal tissues, with expression of these transporters greatly decreased after birth in many of these cell types. In the pre-implantation embryo, GLUT3 is the transporter responsible for the uptake of uterine glucose in mice, though GLUT8 may also play a role (Pantaleon et al 1997;Carayannopoulos et al 2000). High levels of GLUT1 protein are also present in pre-implantation embryos, and by day 6.5 to 7.5 glucose is the main substrate consumed (Houghton et al 1996;Pantaleon et al 2001).…”
Section: Introductionmentioning
confidence: 99%